GDF15 promotes EMT and metastasis in colorectal cancer - Li, Chen; Wang, Jingyu; Kong, Jianlu; Tang, Jinlong; Wu, Yihua; Xu, Enping; Zhang, Honghe; Lai, Maode (Oncotarget, 2016)
Metastasis is the major cause of cancer deaths, and the epithelial-mesenchymal transition (EMT) has been considered to be a fundamental event in cancer metastasis. However, the role of growth differentiation factor 15 (GDF15) in colorectal cancer (CRC) metastasis and EMT remains poorly understood. Here, we showed that GDF15 promoted CRC cell metastasis both in vitro and in vivo. In addition, the EMT process was enhanced by GDF15 through binding to TGF-β receptor to activate Smad2 and Smad3 pathways. Clinical data showed GDF15 level in tumor tissues, and the serum was significantly increased, in which high GDF15 level correlated with a reduced overall survival in CRC. Thus, GDF15 may promote colorectal cancer metastasis through activating EMT. Promisingly, GDF15 could be considered as a novel prognostic marker for CRC in the clinic.